The Analysis of students’ mathematical reflective and critical thinking ability - A Putri; S Fatimah (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research is aimed to students of mathematics education with the purpose to analyze the ability of higher-order thinking at formal operational stage in mathematics learning. This research was conducted by giving tests that can measure the ability of reflective and critical thinking mathematically and interviewing subjects based on their answers. The results obtained are then analyzed to see the student's ability level. Research instrument used is a test of reflective and critical thinking ability, and interview with students. The results showed that students already have a good reflective and critical thinking ability in mathematics learning.